2015
DOI: 10.1016/j.yhbeh.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and phenotypes with estrogen exposures across the lifespan: What does Goldilocks have to do with it?

Abstract: Estrogens impact the organization and activation of the mammalian brain in both sexes, with sex-specific critical windows. Throughout the female lifespan estrogens activate brain substrates previously organized by estrogens, and estrogens can induce non-transient brain and behavior changes into adulthood. Therefore, from early life through the transition to reproductive senescence and beyond, estrogens are potent modulators of the brain and behavior. Organizational, reorganizational, and activational hormone e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 249 publications
(325 reference statements)
1
29
0
Order By: Relevance
“…To add complexity to this puzzle, what is optimal for one woman may not have the same effect in another woman (for review, see Koebele & Bimonte-Nelson, 2015). Our findings provide further insight into the window of opportunity for hormone therapy by revealing that the age at the onset of the menopause transition matters for memory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To add complexity to this puzzle, what is optimal for one woman may not have the same effect in another woman (for review, see Koebele & Bimonte-Nelson, 2015). Our findings provide further insight into the window of opportunity for hormone therapy by revealing that the age at the onset of the menopause transition matters for memory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, there have been numerous review articles underscoring the importance of these factors (Gibbs and Gabor, 2003; Brinton, 2004; Bimonte-Nelson et al, 2010; Rocca et al, 2011; Maki, 2012; Sherwin, 2012; Acosta et al, 2013; Chisholm and Juraska, 2013; Fischer et al, 2014; Luine, 2014; Koebele and Bimonte-Nelson, 2015; McCarrey and Resnick, 2015). The present study adds to the growing consensus that clarity gained from understanding the impact of these parameters is critical for providing information to offer unique and tailored treatment options for women.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens have been shown to have beneficial effects on a myriad of body systems, including cardiovascular, bone, and brain health. However, estrogens’ actions are complex, and often exert beneficial effects only when given at a fitting dose, through the ideal route of administration, and with appropriate timing and duration of the treatment [3032]. In the early 2000’s, findings from the Women’s Health Initiative Memory Study (WHIMS) challenged the tenet that estrogen-containing HT has protective effects against global cognitive decline, mild cognitive impairment, and probable dementia risks when the large, double-blind, placebo-controlled clinical trials indicated that some forms of HT increase the risk of probable dementia development when administered post-menopause [3336].…”
Section: 1 the Human Menopause Transitionmentioning
confidence: 99%